A small molecule that induces translational readthrough of CFTR nonsense mutations by eRF1 depletion - Jyoti Sharma (Nature Portfolio, 2021)
Premature termination codons can cause early translation termination and lead to disease. Here the authors perform a screen to identify compounds with readthrough activity and show that these reduce eRF1 levels to suppress premature termination associated with cystic fibrosis.